Juridical Review of Criminal Acts of Sexual Violence Committed by Lecturers Against Students as One of the Conditions for Graduating Lectures - Resi, Maria Gracela Putri; Heryanto Amalo; Rosalind Angel Fanggi (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the educational institutions that plays an important role in developing Human Resources is Higher Education. Higher education is organized using an open system. In Indonesia, the process of providing education, especially in universities, often deviate from established regulations. One of them is the abuse of power carried out by lecturers towards students (abuse of power). This happens because the lecturer has a higher position than the students, so if it is not used professionally, this power can be misused in certain ways. So, in this research, the main problem of the researcher is how the legal regulation of criminal acts of sexual violence committed by lecturers against students is and what is the mechanism for resolving criminal acts of sexual violence committed by lecturers against students as one of the requirements for passing the final assignment